ANALISIS KEBEBASAN PRODUKSI, DISTRIBUSI PERDAGANGAN BERAS UNTUK MENCAPAI HARGA RASIONAL PERSPEKTIF ETIKA BISNIS ISLAM - Fadli Daud Abdullah; Syahrul Anwar; Dede Kania (Strata Business Review, 2023)
This research analyzes rice trading practices in Islam that can create rational rice prices, involving analysis of the roles of producers and consumers in creating rational prices for society. Rice as a basic food commodity has a central role in meeting human food needs. Changes in rice prices have a significant impact on a global scale, with the potential to influence social and economic stability throughout the world. This research uses qualitative research methods and secondary data analysis. The research result is that the concept of freedom of production and distribution of rice trade in Islamic business professional ethics emphasizes individual freedom in rice trade, with an emphasis on moral and ethical principles. This creates a framework that reflects the principles of morality in economic activities, maintaining a balance between economic and moral aspects. The main goal is to achieve rational prices in rice trade, which not only benefits individuals, but also society as a whole. In this case, business professional ethics in Islam must seek profits in good faith, uphold the principles of morality, respect the rights and interests of other people, and maintain social justice and the interests of society as a whole.